To the formation of the biodiversity of the Russian Far East - V. M. Urusov; L. I. Varchenko (Проблемы ботаники Южной Сибири и Монголии, 2020)
Plants diversity and riches of specific floras in the Russia’s Far East is determined not only and not somuch by a modern ecotopes diversity, as by the expression in the stale of the limit of permafrost soils, by the spread ofconsolidated boreal-nemoral ecosystems, by the situation of the Holocene boundary, ancient and early Holocene, presenceof the "small" and “big” migratory ways promoted the savings of a vascular plants diversity (RSR) by all praterritory, andthe “bridges” of a land. These bridges provided, first, resettlement of plant species from the West in dry late Pleistocene,updating of floras by Daurian-Mongolian steppe species, secondly, by returning of the species lost in the cold periods dueto their migration from the south, from refuges, by presence of refuges from fire, and elementary pyrogenic degradationof flora and vegetation reduces RSR on the order. However to the north from 50º N. L. on continent and Sakhalin islandand with 46º N. L., from Urup island on the Greater Kuril Islands refuges and isolates for maintenance high RSR has novalue or even it reduces, preserving more cold-resistant and cold-loving flora. Poverty of flora of coasts of KamchatkaPeninsula is connected with this phenomenon.